2023
DOI: 10.1055/a-2028-7955
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Resection after Immunochemotherapy Versus Chemotherapy in Oligometastatic Nonsmall Cell Lung Cancer

Abstract: Background Neoadjuvant immunochemotherapy is currently being tested in pivotal trials for stage I-III NSCLC. The impact of immunochemotherapy in patients with oligometastastic disease remains undefined. This study aimed to compare the outcomes of radical treatment after the neoadjuvant course of immunochemotherapy versus chemotherapy. Methods We retrospectively analyzed patients with oligometastastic disease who were treated with immunochemotherapy or chemotherapy combined with local ablation of metastases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
“…While these studies are important, their results cannot formally change the standard of therapy. The evidence ranges from case reports and retrospective series [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] to phase III randomized trials [ 69 ] such as the SINDAS trial. This trial showed that adding SRT to TKIs significantly improves survival in 133 EGFR-mutated NSCLC OMD patients (median OS TKI plus SRT: 25.5 months vs. 17.4 months in TKI monotherapy).…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological types of lung cancer include small cell lung cancer (SCLC) and non–small cell lung cancer (NSCLC), of which NSCLC accounts for 80% to 85% 3,4 . Surgery is the main treatment for resectable NSCLC, but single surgery is not sufficient for most lung cancer patients and requires a combination of adjuvant treatment 5,6 . Therefore, the question of identifying high‐risk patients with postoperative recurrence and metastasis in advance and providing appropriate clinical intervention is a hot topic in academic research.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Surgery is the main treatment for resectable NSCLC, but single surgery is not sufficient for most lung cancer patients and requires a combination of adjuvant treatment. 5 , 6 Therefore, the question of identifying high‐risk patients with postoperative recurrence and metastasis in advance and providing appropriate clinical intervention is a hot topic in academic research. Tumor, node, and metastasis (TNM) stage is the most commonly used prognostic indicator regarding lung cancer in clinical practice, but patients with the same TNM stage do not have the same prognosis.…”
Section: Introductionmentioning
confidence: 99%